STYLISTIC ANALYSIS OF A PORTRAIT OF THE ARTIST AS A YOUNG MAN FROM LEXICAL AND GRAMMATICAL CATEGORY - Ejupi, Vlera; Iseni, Arburim; Siljanovska, Liljana; Hossain, Md. Amir (European Scientific Journal, ESJ, 2014)
Language is a purely human and non-instinctive method of communicating ideas, emotions and desires by means of a system of voluntarily produced symbols. Linguists have recognized that language can be spoken, thought, written, and expressed in shorthand, Morse code, Braille, teleprint code, and even whistled. Each of these ‗codings‘ has been analyzed statistically in numerous ways but the most common approaches are: counting the number of occurrences of words, counting the number of times a word of given length occurs, counting the number of times a sentence of given length occurs, and counting the number of times a word containing a given number of phonemes occurs. The resulting frequency distributions have been used to characterize an author or indeed a language. They have been used to estimate an author‘s total vocabulary. One important feature or by-product of such distributions is that languages of societies can be classified according to some complexity criterion. Since it is possible that the complexity of a society can be indicated by the complexity of its language, then the models for such distributions take on a utility factor besides the intrinsic interest of classification. This paper classifies many linguistic features and reviews some linguistic indicators commonly referred to as words, vocabulary, phrases, clauses, sentences, etc.